2013
DOI: 10.1371/journal.pone.0069270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of HIV Entry into the CNS: Increased Sensitivity of HIV Infected CD14+CD16+ Monocytes to CCL2 and Key Roles of CCR2, JAM-A, and ALCAM in Diapedesis

Abstract: As HIV infected individuals live longer, the prevalence of HIV associated neurocognitive disorders is increasing, despite successful antiretroviral therapy. CD14+CD16+ monocytes are critical to the neuropathogenesis of HIV as they promote viral seeding of the brain and establish neuroinflammation. The mechanisms by which HIV infected and uninfected monocytes cross the blood brain barrier and enter the central nervous system are not fully understood. We determined that HIV infection of CD14+CD16+ monocytes resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
176
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(190 citation statements)
references
References 54 publications
(62 reference statements)
11
176
1
2
Order By: Relevance
“…Our data suggest that ALCAM plays a role in HAM/TSP pathogenesis similar to its role in neuroAIDS. Indeed, in neuroAIDS, ALCAM levels are not altered on the BBB endothelium (18), HIV infection increases ALCAM expression on monocytes (20), and ALCAM blockade by neutralizing antibodies reduces HIV-infected monocyte extravasation in in vitro BBB models (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data suggest that ALCAM plays a role in HAM/TSP pathogenesis similar to its role in neuroAIDS. Indeed, in neuroAIDS, ALCAM levels are not altered on the BBB endothelium (18), HIV infection increases ALCAM expression on monocytes (20), and ALCAM blockade by neutralizing antibodies reduces HIV-infected monocyte extravasation in in vitro BBB models (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…We tested the impact of an anti-ALCAM blocking antibody (used in previous studies [17,19,20]) on the transmigration of T cell lines through a monolayer of human cerebral microvascular endothelial hCMEC/D3 cells cultured on a Transwell device to determine if ALCAM plays a role in the migration of HTLV-1-infected lymphocytes across the BBB. These cells have been extensively used as a relevant in vitro model for the human BBB endothelium (37).…”
Section: Cd25mentioning
confidence: 99%
See 1 more Smart Citation
“…79,80 In uninfected macaques, only 14.1% AE 0.4% of splenic monocytes expressed CD16 ( Figure 4B). This was significantly increased during SIV infection as early as 7 dpi, and peaked at 21 dpi where 88.4% AE 2.0% of cells expressed CD16.…”
Section: Peripheral Blood Monocytes Are Recruited Into the Spleen By mentioning
confidence: 99%
“…Furthermore, we have previously demonstrated that physical hindrance of ALCAM during active EAE, using anti-ALCAM blocking antibodies, delays the progression and reduces the severity of the disease, while also partially preventing the infiltration of leukocytes in the CNS (11). In addition, several groups have demonstrated the involvement of ALCAM in leukocyte transmigration across human BBB-ECs or MBECs (11,12,(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%